Analisis Kebijakan Pemerintah Daerah Tentang Pemberlakuan Sertifikat Vaksin Covid-19 Sebagai Syarat Administrasi di Tempat Umum - Hartati, Hartati; Satoto, Sukamto (Universitas Negeri Malang, 2022)
This study aims to analyze the substance of the Covid-19 vaccine certificate policy as an administrative requirement in Jambi City and the regional government’s authority in enforcing the Covid-19 vaccine certificate policy in Jambi City. This study uses an empirical legal approach with a descriptive research type. Data collection techniques using interviews, observation, and documentation. Source of data used in the form of primary data and secondary data. The data that has been obtained is analyzed systematically. The results of the study show that the Covid-19 vaccine certificate policy as an administrative requirement for entering public places regulated through the Mayor of Jambi Circular Letter Number PW.01/441/DPK/2021 must be pursued into a Regional Regulation so that the substance has strong binding power. The Regional Government of Jambi City in enforcing the Covid-19 vaccine certificate policy has the authority to disseminate information to the community and carry out a real monitoring function as a means to evaluate the performance of implementing the Covid-19 vaccine certificate in public places or public spaces.